The effectiveness of family enrichment model for work on marital satisfaction, career and work-family conflict of married female managers - Afshari, Sedigheh; Bahrainian , Abdolmajid; Shahabizadeh , Fatemeh (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The purpose of this research was to determine the effectiveness of social-emotional skills training on motivational beliefs and self-regulation learning strategies of girls with learning disabilities. Methods: The present research method is practical in terms of purpose and in terms of field situation and in terms of semi-experimental method with the design of pre-test, post-test and follow-up was with the control group and random assignment. The statistical population of this research included all girls aged 10 to 13 with learning disabilities in reading, writing and math in Joybar city in the academic year of 2019-20. Sampling was purposeful and 30 girls were selected as a sample, and then 15 girls were randomly assigned to the social-emotional skills training group and 15 girls were assigned to the control group. The experimental group was trained in social-emotional skills based on the Squires model (2003) for 10 sessions; while the control group did not receive any intervention. Also, Harter’s motivational beliefs questionnaire (1981) and Ryan and Connell’s self-regulated learning questionnaire (1989) were used in the pre-test, post-test and follow-up stages. Finally, the data were analyzed using ANOVA with repeated measures and Bonferroni’s post hoc test. Results: The results showed that social emotional skills training has an effect on girls’ motivational beliefs (F=16.95; P=0.002) and self-regulation learning strategies (F=88.75; P=0.001). Conclusion: It can be concluded that social emotional skills training is effective on girls’ motivational beliefs and self-regulation learning strategies.